Apigenin Attenuates Adriamycin-Induced Cardiomyocyte Apoptosis via the PI3K/AKT/mTOR Pathway. (8th June 2017) - Yu, Wei; Sun, Huirong; Zha, Wenliang; Cui, Weili; Xu, Ling; Min, Qing; Wu, Jiliang
Abstract : Treatment with Adriamycin (ADR) is one of the major causes of chemotherapy-induced cardiotoxicity and therefore is the principal limiting factor in the effectiveness of chemotherapy for cancer patients. Apigenin (API) has been shown to play a cardioprotective role. The present study examined the effect of API on ADR-induced cardiotoxicity in mice. Sixty male Kunming mice were randomly divided into 4 groups: a control group, ADR model group, low-dose API treatment group (125 mg·kg −1 ), and high-dose API treatment group (250 mg·kg −1 ). Blood samples were taken to evaluate a spectrum of myocardial enzymes. Cardiomyocyte apoptosis was measured using a TUNEL assay, and cardiomyocyte autophagy was observed using electron microscopy. Moreover, apoptosis-related proteins, such as Bax and Bcl-2, autophagy-related proteins, including Beclin1 and LC3B, and PI3K/AKT/mTOR pathway-related proteins were examined with western blot. Our results demonstrate that ADR caused an increase in the serum levels of cardiac injury markers and enhanced cardiomyocyte apoptosis and autophagy. API administration prevented the effects associated with ADR-induced cardiotoxicity in mice and inhibited ADR-induced apoptosis and autophagy. API also promoted PI3K/AKT/mTOR pathway activity in ADR-treated mice. In conclusion, API may have a protective effect against ADR-induced cardiotoxicity by inhibiting apoptosis and autophagy via activation of the PI3K/AKT/mTOR pathway.